The Influence of Personality Traits on Household Financial Decisions: Evidence from 31 European Countries - Júlio Lobão; Rashed Isam Ashqar (Revista Galega de Economía)
Household financial decision-making is a complex process influenced by various factors, including personality traits. This study examines the impact of personality traits on household finance across 31 European countries, utilizing the European Union Statistics on Income and Living Conditions (EU-SILC) dataset from Eurostat. We employ logistic regression analysis to investigate the relationship between personality traits and three key dimensions of household finance: the likelihood of holding secured debts, the probability of experiencing financial distress, and the state of financial well-being. Our findings reveal that high levels of neuroticism and extraversion are linked to a greater likelihood of financial distress, whereas low levels of these traits are associated with a higher probability of holding a mortgage. This study highlights the significance of incorporating personality traits into the analysis of household financial decision-making and provides valuable insights into the determinants of household finance in Europe.